2013
DOI: 10.1111/j.1600-048x.2012.05817.x
|View full text |Cite
|
Sign up to set email alerts
|

Alula size signals male condition and predicts reproductive performance in an Arctic‐breeding passerine

Abstract: While studies of achromatic plumage signaling are scarce relative to chromatic ornaments, achromatic ornaments have the potential to act as an efficient form of visual communication due to the highly conspicuous contrast between black and white body regions. Recently, achromatic plumage reflectance has been shown to indicate condition, yet the condition‐dependence of achromatic patch size remains unstudied. Here we show the first evidence that alula size, an achromatic plumage patch, has the potential to signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 50 publications
(64 reference statements)
2
12
0
Order By: Relevance
“…, ), supporting the idea that the earliest arriving females have the broadest choice of breeding partners (Guindre‐Parker et al. ,b). We located all nests, recorded the laying date of the first egg and then subsequent clutch size.…”
Section: Methodssupporting
confidence: 58%
See 2 more Smart Citations
“…, ), supporting the idea that the earliest arriving females have the broadest choice of breeding partners (Guindre‐Parker et al. ,b). We located all nests, recorded the laying date of the first egg and then subsequent clutch size.…”
Section: Methodssupporting
confidence: 58%
“…() reported a negative relationship between song rate and laying date, and Guindre‐Parker et al. () reported that higher quality male plumage signals predicted earlier laying dates. Likewise, Guindre‐Parker et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, previous studies on species possessing both carotenoid‐ and melanin‐based signals may have negatively biased support for the condition‐dependence of melanin‐ relative to carotenoid‐based plumage (although see Parker et al 2003). Recent findings in species that lack any carotenoid plumage ornaments suggest that black plumage may indeed be condition‐dependent (Gladbach et al 2011, Guindre‐Parker et al 2013a). We hypothesized that melanin‐based ornaments are more likely to serve as reliable indicators of condition in species that are achromatic compared to ones that also have a carotenoid‐based trait.…”
mentioning
confidence: 99%
“…At 8 days of age – the day before fledging –we counted the number of nestlings present in the nest as our estimate of the number of fledglings. We trust that this is an accurate estimate of fledging success as there is no nest predation at our island study site and nestling deaths occur due to starvation (discussed in Guindre‐Parker et al ., ). Although these deaths may be related to genetic or health problems, we feel that it is more likely that they represent brood reduction from starvation, as suggested previously for snow buntings (Hussell, ).…”
Section: Methodsmentioning
confidence: 97%